Extinct genus Lagokarpos reveals a biogeographic connection between Tibet and other regions in the Northern Hemisphere during the Paleogene. Issue 6 (26th July 2019) - Tang, He; Liu, Jia; Wu, Fei‐Xiang; Spicer, Teresa; Spicer, Robert A.; Deng, Wei‐Yu‐Dong; Xu, Cong‐Li; Zhao, Fan; Huang, Jian; Li, Shu‐Feng; Su, Tao; Zhou, Zhe‐Kun
Abstract: The biodiversity history on the Qinghai–Tibetan Plateau (QTP) has remained unclear for a long time. Recent paleobotanical investigations provide opportunities for revealing the phytogeographic history on the QTP in deep time and for testing phylogeographic hypotheses. Lagokarpos is an extinct genus with unknown modern affinities. It is easily distinguished by its fruits, which have two long wings and an elliptical fruit body. Previously, Lagokarpos fossils have only been found from North America and Germany, ranging from the latest Paleogene to early middle Eocene. Recently, we found fossil fruits of this genus from the Niubao Formation, near Bangoin County in the central QTP. A new species, namely Lagokarpos tibetensis H. Tang, T. Su & Z. K. Zhou sp. nov., is described. This is the first fossil record of the genus in Asia. The occurrence of L. tibetensis indicates a close floristic linkage between the QTP and other floras in the Northern Hemisphere during the Paleogene. According to the floristic assemblages, we suggest the central QTP experienced a tropical or subtropical humid climate during that period.